Frailty index in the Colonias of the Rio Grande Valley: health related quality of life and resilience - Manusov, Eron G.; Diego, Vincent P.; Williams-Blangero, Sarah (Frontiers in Medicine, 2023)
Frailty is characterized by an accumulation of deficits that lead to vulnerability to adverse health outcomes. The Frailty Index (FI) quantifies frailty by measuring deficits that increase susceptibility to stressors. While over 700 Frailty Indices have been published, only one Frailty Index focuses on Mexican Americans(1). This study focused on a population of Mexican Americans living in vulnerable communities in the Rio Grande Valley of south Texas. It used a Frailty Index developed based on common health-related data--the Patient Health Questionnaire (PHQ-9) and a Health-related Quality of Life survey (HrQoL Duke Health Profile). Quality of life, resilience, and frailty are interrelated and influenced by chronic illness, mental illness, poverty, cognitive impairment, and community support. Lower psychological well-being and excessive treatment of chronic diseases may contribute to frailty and impact quality of life. This study is based on an earlier study describing the usefulness of a Frailty Index specific to Mexican Americans in South Texas(1) and the role of HrQOL related to frailty. The results indicate that HrQoL is a significant predictor of frailty in this population. Men and women show differences in the prevalence of chronic conditions and domains of Health-related Quality of Life. The study highlights the importance of addressing modifiable mental health and social stressors to reduce frailty. Furthermore, it suggests that factors supporting resilience and well-being, such as physical and mental health, social support, and perceived health, play a crucial role in frailty development. The findings have implications for interventions targeting vulnerable populations and emphasize the need for further research on the relationship between Health-related Quality of Life and frailty.